Czas na komediowej scenie (Ter. An., Ht., Ph.) - Skwara, Ewa (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
This article presents the methods used by Terence to control theatrical time, which is not identical to astronomical time (that is the actual time of the presentation). Most frequently, the comic poet strives to compress scenic time in order to accommodate events lasting a hole day within the span of a spectacle lasting 2-3 hours. To this end the poet above all avoids repetitions, and if certain information has to be forwarded to the next character, then this happens off-stage. Furthermore, the play is acted out simultaneously in two threads – one act being staged before the audience, and the other off-stage, which the audience does not actually view but is only informed of. The comic poet also shapes the speed at which events take place – most often speeding things up. He makes use of what was then a theatrical convention, which was based on the idea that time off-stage passes more quickly (characters who say they are going to the forum return from there within a few minutes). Only occasionally is the tempo of the comedy released (when the overly quick movement of a character would undermine the probability of events). These techniques have on the one hand the aim of using time economically, and on the other of making the action more gripping.
Keywords: Plaut; Terencjusz; komedia rzymska; 'czas' dramatyczny